Effect of exogenous melatonin on endocrinological profiles, biochemical and antioxidant and oxidative stress profiles in post-partum anestrus Andaman local buffaloes (Bubalus bubalis) in tropical island ecosystem - PERUMAL, P; DE, A K; BHATTACHARYA, D; ALYETHODI, R R; BHOWMICK, SNEHA; KUNDU, A (The Indian Journal of Animal Sciences, 2021)
Andaman local buffalo (ALB) is distributed in Andaman and Nicobar Islands. ALB is non-descriptive and represents admixture of different Indian breeds of buffaloes. ALB is suffering infertility due to anestrus in dry (summer) season. Therefore, this study was conducted to assess the effect of slow release subcutaneous exogenous melatonin (MT) implant on hematological profiles, endocrinological profiles (cortisol and prolactin), biochemical profile (total protein, albumin, globulin, glucose and total cholesterol), antioxidant profiles [total antioxidant capacity (TAC), catalase (CAT), glutathione (GSH) and superoxide dismutase (SOD)] and oxidative stress profile (malondialdehyde; MDA) in anestrus buffalo cows during summer to improve its reproductive efficiency. Experimental buffaloes (5–7 years of age) were selected and divided into two groups, Gr I: Control (n=6) and Gr II: Treatment (n=6; melatonin implant @ 18 mg/50 kg b.wt). Statistical analysis revealed that these experimental profiles differed significantly between treatment and control groups. Blood profiles revealed that anestrus buffalo suffered severe macrocytic hypochromic anemia with increased leukocytosis and MT has improved the health status of reproductive system and whole body systems. Concentration of cortisol and prolactin were lower in MT treated than in control group. Similarly, antioxidant profiles were higher and oxidative stress profile was lower in MT treated group than in control group. Biochemical profiles were increased in MT treated than in untreated buffalos. Study concludes that melatonin had significant beneficial effects in improvement of the antioxidant profiles, minimization of oxidative stress with cascading beneficial effects on hormone, biochemical and hematological profiles, which will improve the cyclicity and fertility rate in anestrus buffalo during summers in humid tropical island ecosystem.